Coastal resort dynamics and the tourism informal segment : case study analysis of Phuket, Thailand. - Tan, Karen Pei-Sze. (2008)
Coastal tourism has been a perennial favourite with tourists worldwide since the eighteenth century. Although the reasons fuelling such interest have since changed, the popularity of coastal tourism remains undisputed. Within Southeast Asia, most coastal sites are proximate to culturally and geographically rich hinterlands, thus increasing their attractiveness.